Monitoring DNA-Ligand Interactions in Living Human Cells Using NMR Spectroscopy - Krafcikova, Michaela; Dzatko, Simon; Caron, Coralie; Granzhan, Anton; Fiala, Radovan; Loja, Tomas; Teulade-Fichou, Marie-Paule; Fessl, Tomas; Hänsel-Hertsch, Robert; Mergny, Jean-Louis; Foldynova-Trantirkova, Silvie; Trantirek, Lukas (Journal of the American Chemical Society, 2019)
Studies on DNA-ligand interactions in the cellular environment are problematic due to the lack of suitable biophysical tools. To address this need, we developed an in-cell NMR-based approach for monitoring DNA-ligand interactions inside the nuclei of living human cells. Our method relies on the acquisition of NMR data from cells electroporated with preformed DNA-ligand complexes. The impact of the intracellular environment on the integrity of the complexes is assessed based on in-cell NMR signals from unbound and ligand-bound forms of a given DNA target. This technique was tested on complexes of two model DNA fragments and four ligands, namely, a representative DNA minor-groove binder (netropsin) and ligands binding DNA base-pairing defects (naphthalenophanes). In the latter case, we demonstrate that two of the three in vitro-validated ligands retain their ability to form stable interactions with their model target DNA in cellulo, whereas the third one loses this ability due to off-target interactions with genomic DNA and cellular metabolites. Collectively, our data suggest that direct evaluation of the behavior of drug-like molecules in the intracellular environment provides important insights into the development of DNA-binding ligands with desirable biological activity and minimal side effects resulting from off-target binding.
Keywords: Cell Survival; Ligands; párování bází; Humans; ligandy; Naphthalenes; Nuclear Magnetic Resonance, Biomolecular; nukleární magnetická rezonance biomolekulární; Netropsin; naftaleny; Base Pairing; Anti-Infective Agents; antiinfekční látky; vazebná místa; lidé; netropsin; Binding Sites; buněčné linie; DNA; objevování léků; Cell Line; konformace nukleové kyseliny; Nucleic Acid Conformation; Drug Discovery; viabilita buněk